GEOINFORMATIC SYSTEMS IN THE STUDY AND RESEARCH OF WINDS (IN THE SYRDARYA REGION AS AN EXAMPLE) (Scientific journal of the Fergana State University, 2026)
The article provides information on annual, monthly and daily wind directions and speeds in the Syrdarya region. It also briefly describes the sources of data on wind movement and direction and their differences from meteorological observation point data. It also provides detailed information on the advantages and features of using GIS technologies in the formation of wind maps of regions using the example of Syrdarya region.